Unraveling the role of plant growth-promoting bacteria in recruiting microbiome from maize rhizosphere - Ferrarezi, Jessica Aparecida (2024)
The beneficial plant-microbe associations have been widely explored with the purpose of understanding the mechanisms involved in this interaction, in order to develop bioinoculants for agriculture aiming at sustainability and reduction of chemical inputs use. Plant growth promoting bacteria (PGPB) have been reported as interesting alternatives to mineral fertilizers for a range of crops. The strains Azospirillum brasilense Ab-V5 and Bacillus thuringiensis (Bt) RZ2MS9 have shown significant effect in plant growth promotion, and for that they are classified as PGPB. However, the lack of holistic comprehension of PGPB-plant-native soil microbiome can lead to inconsistency of results in field conditions. Recent ecological theories reveal that plant microbiomes are organized as microbial hubs with keystone species and helpers. These microbial networks are strongly connected, molecularly modulated and can influence plant metabolism and physiology. The molecular modulation of such association can be accessed with the advance of high throughput sequencing and phenotyping technologies. It has been possible to access information about the plant-associated bacterial community (including those non-cultivable), correlate it with the main microbiota-modulating factors and physiological responses under influence of biostimulants. Thus, through metataxonomics, metagenomics and phenomics, the objective of this work is to characterize the microbial community associated with maize under influence of the potential keystone PGPB A. brasilense Ab-V5. The unprecedented approach through integration of omics data and a holistic view of the complex inoculant-plant-microbiome system were crucial to support the original development of a synthetic bacterial community (SynCom) with the purpose of promoting plant growth. To understand the role of A. brasilense Ab-V5 in microbiome, we conducted greenhouse experiments with metagenomics data, we dissected the potential naturally occurring microorganisms as PGPB candidates by assembling and characterizing high-quality metagenome-assembled genomes. We created a new collection of PGPB candidates by isolating, characterizing and selecting members from the native soil community from maize-cultivated field (CNM). The strain Arthrobacter sp. CNM05 demonstrated high potential as PGPB with a range of phenotypic attributes evaluated in vitro and in silico through genomic sequencing. With the addition of selected strains from the EMBRAPA database (AleloMicro), we designed and tested an omics data-driven SynCom. The results show that the inoculation of SynCom promoted faster germination of maize seeds compared to non-inoculated treatment. Furthermore, root and shoot traits responded positively to the SynCom+Ab-V5 application. Our results indicate that the development of the SynCom based on omics data is a promising approach to optimize the beneficial effects of inoculants for plant growth promotion. In addition, we also conducted a greenhouse experiment to evaluate the role of the gene aiiA encoder of acyl-homoserine lactonase (a molecule involved in quorum quenching-QQ system of Bt RZ2MS9), in interaction with the native bacterial community. We used a mutant Bt RZ2MS9 ΔaiiA previously obtained with CRISPR-Cas9. Our results indicate that QQ activity is an important mechanism for PGPB persistence in the rhizosphere. This implies the ability of PGPB to interfere with quorum sensing communication of other bacteria species might be relevant for the establishment of Bt RZ2MS9 in the native microbial community and, consequently, might be key for plant growth promotion and soil native microbiome modulation.